TEOLOGI RAHIM MENURUT CHOAN SENG-SONG SUATU REFLEKSI KRITIS - Eramartina martina Saragih (Jurnal Ledalero, 2022)
Abstract: The Asian reality is characterized by religious and cultural diversity. Social changes and especially poverty are the complexities they contain. In such circumstances, the Church is called to face this reality. Theologians are trying to find an understanding of theology that fits the Asian context. C.S. Song is an Asian theologian who tries to respond to this reality with a thought about the theology of Rahim that he explains using the narrative method.The theology of Rahim is a theology that guides humans to God's love and suffering and leads humans to freedom, justice and peace. The basic premise of Rahim's theology is contained in Passio: Passio as the starting point of theology, Rahim as Passio's "Mountain of Fire", and the disappearance of Passio in Christian Theology. Passio means love and suffering. Passio becomes suffering when faced with the reality of poverty, oppression, and it is precisely through that suffering that Passio becomes true love. Through the above understanding, the Church is called to realize its mission as a prophet who can present the Kingdom of God in the lives of the faithful. C.S. Song through the Theology of Rahim invites every believer to participate in realizing the Kingdom of God in the world. This participation should give birth to solidarity for others who are suffering, oppressed and exploited.Keywords: Asian Theology, poverty, suffering, Passio, Choan Seng-Song, Womb Theology